HUKUM DALAM MENDORONG DINAMIKA PEMBANGUNAN PEREKONOMIAN NASIONAL DITINJAU DARI PRINSIP EKONOMI KERAKYATAN - Hapsari, Dwi Ratna Indri (Legality : Jurnal Ilmiah Hukum, 2018)
Article 33 paragraph (4) of the 1945 Indonesian Constitution, "The national economy which is regulated based on economic democracy with the principle of togetherness, efficiency, justice, support, environmental insight, independence, and also with financial assistance in various large business activities, cheap, and small in the business partnership pattern ". The concept of the Indonesian national economy commenting on us together and explicitly in our constitution adhering to the principle of kinship agreed upon can be found in Article 33 paragraph (4) of the 1945 Indonesian Constitution, people's sovereignty also promotes Pancasila. As a developing country Indonesia cannot escape the era of globalization, international free trade. However, what makes the challenge is that Indonesia can still keep up with the flow of globalization but still in the populist economic corridor that has been conceptualized in the state constitution concerning national economic development. Law in this case has a special stake in efforts to grow the economy of a country in order to achieve national economic development.